Mystical ineffability: a nonconceptual theory - Gäb, Sebastian (International journal for philosophy of religion, 2024)
This paper discusses the nonconceptual theory of mystical ineffability which claims that mystical experiences can’t be expressed linguistically because they can’t be conceptualized. I discuss and refute two objections against it: (a) that unconceptualized experiences are impossible, and (b) that the theory is ad hoc because it provides no reason for why mystical experiences should be unconceptualizable. I argue against (a) that distinguishing different meanings of ‘object of experience’ leaves open the possibility of non-empty but objectless nonconceptual experiences. I show that (b) is a valid objection but can be countered by a new theory of mystical non-conceptuality: mystical experiences are not conceptual because the specific mode of mystical consciousness prevents conceptualization. The dissolution of the subjectivity of consciousness during mystical experiences undermines the very foundation of the possibility of conceptual thought and thus renders them ineffable.